(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
From humble beginnings, India’s film industry has grown into a significant economic and cultural force. Piracy is the industry’s most serious problem. In terms of films produced and tickets sold, the Indian film industry has grown to become the world’s largest, as well as the sixth-largest in terms of box office receipts and the second-fastest-growing overall. Every day, millions of people around the world watch Indian films. In this post, we’re not only talking about viewers in our own country; rather, we’re focusing on the bigger issue of bringing a diverse audience from all around the world together. As a result, it’s important to remember that the majority of people come from a variety of ethnic and social backgrounds, and many have been Hindi film lovers for over fifty years.